2014
DOI: 10.1371/journal.pone.0090877
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Selective Biosensor with Nanomolar Sensitivity Based on Cytokinin Dehydrogenase

Abstract: We have developed a N 6-dimethylallyladenine (cytokinin) dehydrogenase-based microbiosensor for real-time determination of the family of hormones known as cytokinins. Cytokinin dehydrogenase from Zea mays (ZmCKX1) was immobilised concurrently with electrodeposition of a silica gel film on the surface of a Pt microelectrode, which was further functionalized by free electron mediator 2,6-dichlorophenolindophenol (DCPIP) in supporting electrolyte to give a bioactive film capable of selective oxidative cleavage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Because biosensors are calibrated, their output value is concentration, but this value may not represent the concentration of a single molecular species. For example, Tian et al (124) showed that the use of CKX confers high selectivity for CKs, excluding other prevalent purines; however, there are many CKs, and a biosensor gives a value that is the integral of all substrates present. The CKX biosensor was calibrated using isopentenyladenosine (iP), and a unit of iP equivalents was then defined to account for the CKX signal gained from CK ribosides as well as free bases (124).…”
Section: Comparison Between and Validation Of Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because biosensors are calibrated, their output value is concentration, but this value may not represent the concentration of a single molecular species. For example, Tian et al (124) showed that the use of CKX confers high selectivity for CKs, excluding other prevalent purines; however, there are many CKs, and a biosensor gives a value that is the integral of all substrates present. The CKX biosensor was calibrated using isopentenyladenosine (iP), and a unit of iP equivalents was then defined to account for the CKX signal gained from CK ribosides as well as free bases (124).…”
Section: Comparison Between and Validation Of Methodsmentioning
confidence: 99%
“…For example, Tian et al (124) showed that the use of CKX confers high selectivity for CKs, excluding other prevalent purines; however, there are many CKs, and a biosensor gives a value that is the integral of all substrates present. The CKX biosensor was calibrated using isopentenyladenosine (iP), and a unit of iP equivalents was then defined to account for the CKX signal gained from CK ribosides as well as free bases (124). Validation by MS showed very good agreement between the biosensor iP equivalent value and the MS data once the latter had been converted to iP equivalents by summing the concentrations of each component compound.…”
Section: Comparison Between and Validation Of Methodsmentioning
confidence: 99%
“…Simple amperometric biosensor developed by graphite coated with polypyrrole (PPy) for the determination of salicylic acid in samples of plasma and milk [100]. A real time highly selective nanobiosensor developed for determination of cytokinins and auxion concentrations in tomato xylem sap exudates [101,102]. It is recommended that precautions are better than cure or remedies in case of plant stresses otherwise at the calamity stage it will cause huge crop loss and poor quality of the produce.…”
Section: Nanobiosensor In Crop Stress Managementmentioning
confidence: 99%